Friendly foes: Hybrid gangs or social networking. (November 2014) - Bolden, Christian L.
Hybrid gangs have been identified as having organizational processes that differ from traditional gangs. This study comparatively examines structural processes and characteristics of gangs in a chronic gang city, San Antonio, and an emerging gang city that would be more likely to have "hybrid" gangs, Orlando. A limited number of recent studies have indicated that some gangs may better fit into a social network framework, which calls into question presumptions about hybrid gangs. In this analysis, cooperation between gang members from rival gangs is examined through a social network lens, and findings indicate that such cooperation is a normalized process in the gang landscape.